Muscle strengthening intervention for boys with haemophilia: Developing and evaluating a best‐practice exercise programme with boys, families and health‐care professionals. (17th August 2020) - Hashem, Ferhana; Stephensen, David; Drechsler, Wendy I.; Bladen, Melanie; Carroll, Liz; Tracy, Pellatt‐Higgins; Saloniki, Eirini‐Christina
Abstract: Background: Muscle strengthening exercises have the potential to improve outcomes for boys with haemophilia, but it is unclear what types of exercise might be of benefit. We elicited the views of health‐care professionals, boys and their families to create and assess a home‐based muscle strengthening programme. Objective: To design and develop a muscle strengthening programme with health‐care professionals aimed at improving musculoskeletal health, and refine the intervention by engaging boys with haemophilia and their families (Study 1). Following delivery, qualitatively evaluate the feasibility and acceptability of the exercise programme with the boys and the study's physiotherapists (Study 2). Design: A person‐based approach was used for planning and designing the exercise programme, and evaluating it post‐delivery. The following methods were utilized: modified nominal group technique (NGT) with health‐care professionals; focus group with families; exit interviews with boys; and interviews with the study's physiotherapists. Results: Themes identified to design and develop the intervention included exercises to lower limb and foot, dosage, age accommodating, location, supervision and monitoring and incentivization. Programme refinements were carried out following engagement with the boys and families who commented on: dosage, location, supervision and incentivization. Following delivery, the boys and physiotherapists commented on progression and adaptation, physiotherapist contact, goal‐setting, creating routines and identifying suitable timeframes, and a repeated theme of incentivization. Conclusions: An exercise intervention was designed and refined through engagement with boys and their families. Boys and physiotherapists involved in the intervention's delivery were consulted who found the exercises to be generally acceptable with some minor refinements necessary.